Is Geothermal Power Plant (PLTP) on Mount Slamet Necessary? - Biko Nabih Fikri Zufar; Ahmad Fadli Azami (CV. Literasi Indonesia, 2021)
This article intends to reflect on the construction of a Geothermal Power Plant (PLTP) on Mount Slamet. The construction of the PLTP has been rejected by the Banyumas community, especially the slope communities there. During the exploration process for the power plant, the people on the slopes of Mount Slamet experienced various impacts. Starting from the murky water, forest animals entering the villages, so that material losses cannot do business. This article reviews the phenomenology of how important the development of PLTP is in the midst of a surplus of electricity in Java Island. The findings in this article identify flaws in procedures from planning to implementation. The plan is to do legal acrobatics so that it is easy to get project permits. When doing exploration, it has a significant impact on the community on the slopes of Mount Slamet. Therefore the article tries to provide suggestions or input to local and central governments for; make an objective Environmental Impact Analysis (AMDAL), involve professional parties to conduct academic studies, involve the community or NGOs when determining the PLTP project, conduct intensive and periodic outreach to the community, and provide compensation to the affected communities.